Freestyle Bearing: Work, Play, and Synergy in the Practice of Everyday Life Among Mongolian Reindeer Pastoralists - Rasiulis, Nicolas (Université d'Ottawa / University of Ottawa, 2016)
Approximately 200 people, mostly Dukhas of Tuvan ancestry, live nomadically with reindeer, horses, and dogs as ‘Tsaatans’ in the taiga of northern Mongolia. How do they effectively realize their livelihoods? Does qualifying corporeal manners, or bearings, in which livelihood practices are performed in the moments of actualization offer insight into ways in which longer-term decision-making processes like nomadic settlement and livestock management are embodied? Informed by a phenomenological approach in anthropology during nearly four months of cooperative co-habitation with Tsaatan mentors, I argue that Tsaatans effectively realize livelihood practices as they cheerfully embody poised improvisation and acrobatics in both skillful discernment and movement. Simultaneously anticipating and performing diverse tasks in playful cooperation with friends, family and other animals along nomadic lifestyles in a wilderness habitat involves persistent, sensory-rich, versatile manipulation of environmental materials, as well as extensive geographic knowledge and frequent experiences of risk in remote, rugged terrain and powerful meteorological conditions impossible to completely avoid. These lifestyles catalyze the development of quick-witted and materially sensitive resilience with which people are capable of corresponding with beings, materials, and situations, and thereby of continuing to develop ancestral traditions of reindeer husbandry in a rapidly changing social, economic, technological and geo-political context.